Sexual behavior and HIV infection among pregnant hilltribe women in northern Thailand - Tawatchai Keereekamsuk (2018)
A case-control study was carried out to determine factors associated with HIV infection among pregnant hilltribe women who attended the antenatal clinics of six hospitals in northern Thailand (Mae Suai, Wieng Pa Pao, Mae Sai, Mae Chan, Wieng Kaen, Mae Fa Luang, and Chiang Rai hospitals) between 1 January 2005- 31 May 2007. Data were collected using questionnaires and analysis was by univariate (p-value=0.100) and multivariate analysis (p-value=0.050) in the model of unconditional multiple logistic regression. The ratio of cases to controls was 1:4. The sample consisted of 255 subjects; 51 cases and 204 controls. The mean age of the women was 26.9 years (min=15, max=52, and SD 7.3). The majority of the women were Lahu (49.8%) or Akha (36.9%). Nearly half the women were Christian (48.2%), followed by Buddhist (42.4%). Most of the women were not educated (60.4%). The largest group for family income was 10,000-49,999 baht/year (62.6%). After controlling for family income, family debt, education, occupation and household members, the findings showed that the "not married to debut partner" group were at greater risk than the "married to debut partner" group by 6.6 times (ORadj =6.6, 95%CI=2.9-14.9). The "use of alcohol" group were at higher risk by 4.5 times (ORadj =4.5, 95%CI=2.0-10.3) compared to the no alcohol use group, and a history of genital ulcer group had an increased risk of 6.3 times (ORadj =6.3, 95%CI=1.2-31.1) the chance of having HIV infection compared to no history of genital ulcers in pregnant hilltribe women.